Decomposing Child Poverty Reduction. Issue 1 (March 2014) - Bradshaw, Jonathan; Huby, Meg
European countries vary in the extent to which they succeed in reducing poverty using social transfers. However, we do not have good ways of understanding how these different outcomes are achieved. It is therefore very difficult to learn lessons from abroad. This paper uses micro data from the EU Statistics on Income and Living Condition (SILC), and attempts to decompose reductions in child poverty rates and gaps into the contribution made by children, old age, social exclusion, housing and work-related benefits. The analysis is undertaken for all families with children under 16, lone parent families, couple families, and then for families with varying levels of work intensity. Transfers make a substantial contribution to reducing child poverty rates and closing poverty gaps. The contribution varies between countries in the European Union. There is no single model, no most successful exemplar. Some countries do better for their children in lone parent households and others do better for their children in couple households. The analysis has enabled some opening up of the how question, though what is going on is still something of a mystery in some countries. It is probable that analysis at the national level with greater knowledge of national benefits systems is necessary to further open the 'black box'.